Endoscopic dacryocystorhinostomy for nasolacrimal duct obstruction: an assessment of post-operative outcomes at a tertiary health care centre - Dantuluri, R. K. L. N. Raju (International Journal of Research in Medical Sciences, 2021)
Background: Endoscopic dacryocystorhinostomy (Endo DCR) is a well-established surgical treatment for nasolacrimal duct obstruction (NLDO) cases. Advances in surgical technique and a better understanding of the anatomy have resulted in improvement of the success rate. The objective of this study is to assess the factors responsible for the recurrence of nasolacrimal system obstruction by evaluating the post-operative outcomes of Endo DCR at a tertiary health care centre. Methods: A retrospective study was conducted in the department of ENT, GVP IHC and MT, Visakhapatnam – Andhra Pradesh on 52 patients who underwent Endo DCR procedure from September 2018 to September 2021. The data regarding lacrimal drainage system, operative details, surgical outcomes and complications were analysed. Results: Fifty-two patients (18 male and 34 female) underwent 63 Endo DCR surgeries for NLDO. Success was achieved in 50 cases (79.4%), and failure in 13 (20.6%). Of the 13 failed cases, anatomical obstruction at the fistula site was found in 6 (46.2% of failed cases), whereas functional failure with no evidence of obstruction was found in 7 (53.8%). Conclusions: The success rate appears to be influenced by preoperative parameters like clinical as well as radiological examination of eye and nose; ruling out intraoperative conditions like sinusitis, deviated nasal septum, polyps. These are essential for better coordinating therapeutic expectations and better patient selection. Endo DCR proved to be a safe invasive procedure as it has direct approach to the sac and produced excellent results without any external scar.